2021
DOI: 10.21203/rs.3.rs-234724/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poor weight gain and its predictors among preterm neonates admitted at Muhimbili National hospital in Dar-es-salaam, Tanzania from September 2018 to February 2019

Abstract: Background: Preterm delivery is among the major public health problems worldwide and the leading cause of morbidity and mortality among neonates. Postnatal poor weight gain, which can contribute to mortality, can be influenced by feeding practices, medical complications and quality of care that is provided to these high-risk neonates. This study aimed to investigate the proportion and predictors of poor weight gain among preterm neonates at Muhimbili National Hospital (MNH), from September 2018 to February 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Initiation of the rst feed on the rst day of life had 3 times more adequate postnatal weight gain than those whose initiation was on the second day and beyond among the preterm VLBW neonates. This nding has been demonstrated in other studies conducted in Iran and Tanzania (9,13,14),which showed that early initiation of the enteral feeds was associated with faster growth rates compared to those who were delayed. This is due to early initiation of feeding being associated with early maturation of the intestinal villi and tolerance of the enteral feeds.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Initiation of the rst feed on the rst day of life had 3 times more adequate postnatal weight gain than those whose initiation was on the second day and beyond among the preterm VLBW neonates. This nding has been demonstrated in other studies conducted in Iran and Tanzania (9,13,14),which showed that early initiation of the enteral feeds was associated with faster growth rates compared to those who were delayed. This is due to early initiation of feeding being associated with early maturation of the intestinal villi and tolerance of the enteral feeds.…”
Section: Discussionsupporting
confidence: 77%
“…The sample size was calculated using Open Epi-info Version 7.2.5 considering 95% con dence interval and 80% power. The larger sample size(213) was achieved by using the double population proportion formula considering the percent of adequate weight gain by VLBW infants whose rst feed is within 24 hours(38.3%),RR = 2.2 and percent of adequate weight gain by VLBW infants whose rst feed is longer than 24 hours(17.4) from a study conducted in Tanzania (9). Systematic random sampling technique was used to select cards of preterm VLBW neonates from each hospital.…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation